2020
DOI: 10.3390/ijerph17030987
|View full text |Cite
|
Sign up to set email alerts
|

Setting Priorities to Inform Assessment of Care Homes’ Readiness to Participate in Healthcare Innovation: A Systematic Mapping Review and Consensus Process

Abstract: Organisational context is known to impact on the successful implementation of healthcare initiatives in care homes. We undertook a systematic mapping review to examine whether researchers have considered organisational context when planning, conducting, and reporting the implementation of healthcare innovations in care homes. Review data were mapped against the Alberta Context Tool, which was designed to assess organizational context in care homes. The review included 56 papers. No studies involved a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 81 publications
(186 reference statements)
4
44
0
Order By: Relevance
“…84 This includes assessing care home readiness and capacity to engage, including releasing all levels of staff to engage in intervention design. 143…”
Section: Might This Intervention Be Useful To Residential Care Homes?mentioning
confidence: 99%
“…84 This includes assessing care home readiness and capacity to engage, including releasing all levels of staff to engage in intervention design. 143…”
Section: Might This Intervention Be Useful To Residential Care Homes?mentioning
confidence: 99%
“…SPACE also focused on facilitating positive changes to working culture by applying approaches that emphasised the role of leadership, capacity building and sharing of best practices. The co-design element of programme activities between facilitators and care home staff was reported as particularly important, and has been noted by others as a key means of embedding QI within organisations where active engagement from managers and staff is required for practice changes to be implemented [ 38 , 40 , 41 ]. Indeed, the influence of care home leadership on QI is often cited in the patient safety literature [ 42 ], and other similar programmes have found managerial leadership and care home capacity to engage with QI to be important influences on uptake and involvement [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this pilot study, we found the same barriers and facilitators pointing out the importance of setting the right preconditions for implementation in the nursing home context, throughout research and policy. This might be done by primordially evaluating nursing home readiness in order to increase the use and correct application of the quality indicators [ 55 ].…”
Section: Discussionmentioning
confidence: 99%